RESEARCH ON REGION OF MATURATION ANOMALY AND FORMATION TIME IN ORDOS BASIN - Ren Z.; Zhang S.; Gao S.; Cui J.; Liu X. (My University, 2006)
The Ordos basin on late Mesozoic exist on a tectonic heat event. Based on analysis of the measured data about a great deal of vitrinite reflectance, age of igneous rock, age of apatite fission track,this paper study the time of the occurrence, existent region and the formation machanism of the tectonic heat event. It is determined that distributin of geothermal anomalous region on late Mesozoic era in ordos basin is Wuqi - Qingyang - Fuxian at the sourth of basin. It is decided that tectonic heat event occurred on 100-140 Ma of early Cretaceous period in late Mesozoic, continuous time of tectonic heat event is about 10-40 Ma. Occurrence of tectonic heat event on late Mesozoic in Ordos basin result from intensive thermal mobility of deep lithosphere on the late Mesozoic, Thermal mobility of deep lithosphere in sourth region is stronger than in north region. Mantle occur underplating and thickness of lithosphere reduce, magma invasion and eruption occur on late Mesozoic. Ordos basin be in weak extension environment on late Mesozoic. Formation of anomalous geothermal field has something to do with intensive thermal mobility of deep lithosphere in Ordos basin which resuts from intensive tectonical activity of Qinling orogenic belt on late Yangshanian period.
Keywords: APATITE FISSION TRACK; GEOTHERMAL ANOMALY; GEOTHERMAL GRADIENT; ORDOS BASIN; TECTONIC HEAT EVENT; VITRINITE REFLECTANCE; Мезозой::Меловая; Mesozoic::Cretaceous